The Fermented Dragon Fruit Flour and Commercial Rations For The Carcass and The Part of Carcass Lohmann Brown Aged 21 - 25 Weeks - D,, Camelia; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019, 2019)
This study aims to determine the effect of the use of rations contains fermented dragon fruit flour on carcass weights and part of carcass Lohmann Brown aged 21-25 weeks. This study has been conducted at Teaching Farm Animal Science Bukit Jimbaran, Badung, Bali for four weeks. This study used Completely Randomized Design (CRD) with 3 treatments, each treatment using 5 replication and uses 3 chickens. The treatment that has been given was: R0 (the chicken without fermented dragon fruit flour) R1 (the chicken gave rationed with 5% fermented dragon fruit flour) R2 (the chicken give commercial ration). Variables observed in this study: cut weights, carcass weight, carcass percentages and part of carcass (chest, back, wing, thigh). Studies show the fermented dragon-skin administration by 5% the difference is not significant (P>0.05) to the weight of cut, the weight of carcass, the carcass of percentage and the part of chest, back, wing, thigh. Based on studies, it can be concluded that fermented dragon fruit flour is obtained and the commercial rations have no effect on the carcass and part of carcass Lohmann Brown chicken from 21 - 25 weeks. Keywords: Lohmann Brown chicken, fermented dragon fruit skin flour, carcass, carcass part